1975
DOI: 10.1002/chin.197535014
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: OXYGEN PERMEABILITY OF STABILIZED ZIRCONIA SOLID ELECTROLYTES

Abstract: Die Sauerstoffdurchlässigkeit der Festelektrolyte 85 (Mol‐%) ZrO2 + 15 CaO, 90 ZrO2 + l0 Y2O3, 89 ZrO2 + 8 Y2O3 + 3 Al2O3, 90 ZrO2 + 10 Sc2O3 wird zwischen 900 und 1250°C und Sauerstoffpartialdrücken von 0,01 bis 1,0 atm untersucht.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1985
1985
1985
1985

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…[2]. The expected 1/4 power oxygen pressure dependence of the permeability was observed by Smith et al (7), Fisher (9), Palguev et al (11), and Iwase et al (12). An exponent of 1/3 was reported by Heyne and Beekmans (3), who suggested that the observed deviation from 1/4 might be due to either a different incorporation mechanism for the electronic defects or to partial rate control by a surface reaction.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…[2]. The expected 1/4 power oxygen pressure dependence of the permeability was observed by Smith et al (7), Fisher (9), Palguev et al (11), and Iwase et al (12). An exponent of 1/3 was reported by Heyne and Beekmans (3), who suggested that the observed deviation from 1/4 might be due to either a different incorporation mechanism for the electronic defects or to partial rate control by a surface reaction.…”
mentioning
confidence: 64%
“…7 at fixed P'o2 and variable thickness (T = 1230~ It is seen that the activation energies for bulk diffusion and for surface reaction are very similar. From the expression for/~, the following expression may be obtained (3,12,13) for the electronic conductivity o -~ at 1 atm 195 -+ 10 k J/tool in o -~ (~-Ucm-') = (10.9 _+ 3.4) - [11] RT The activation energy may be compared with the following values (in kilojoules per mole) from the literature: 217 (2), 183 (3), 233 (7), 232 (9), 263 (10), 155 (11), and 98 (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation